PENGARUH PENGGUNAAN MEDIA VIDEO EDUKASI TERHADAP HASIL BELAJAR PKN SISWA KELAS VII SMP NEGERI 2 GONDANGREJO - ., Turyati; Muchtarom, Moh.; ., winarno (PKn Progresif, 2016)
This research aimed to examine whether or not there was an effect of education media video on the learning outcome of the 7th graders of SMP Negeri 2 of Gondangrejo in the school year of 2015/2016 in Basic Competency explaining the essence of freedom of speech. This study was a quantitative research with experimental method. Experimental method used was posttest only control design. The population of research was all of the 7th graders of SMP Negeri 2 of Gondangrejo consisting of 5 grades. The sample was taken using cluster random sampling technique, and 64 students were obtained as the sample divided equally (32 students for each class) into two classes: experiment and control. The data collection was carried out using documentation and observation techniques for data of education video media and objective test for data of students? learning outcome. Prerequisite test used was normality and homogeneity tests. Technique of analyzing data used was two-independent sample t test. Considering the result of research, the mean learning outcome of students was 82.5313 in experimental and 70.1563 in control classes. The result of t-test at significance level of 5% showed that tstatistic > ttable 4.632056 > 1.99897, thus Ho was not supported and Ha was not supported. It showed that there was a difference of learning outcome between experiment and control classes. The mean value showed that the learning outcome of students in experiment class was higher than that in control class. Considering the elaboration above, it could be concluded that there was an effect of education video media on the learning outcome of the 7th graders of SMP Negeri 2 of Gondangrejo in the school year of 2015/2016 in Basic Competency explaining the essence of freedom of speech.